2017
DOI: 10.1080/13613324.2017.1395330
|View full text |Cite
|
Sign up to set email alerts
|

Role models without guarantees: corrective representations and the cultural politics of a Latino male teacher in the borderlands

Abstract: In recent years mentorship has become a popular 'solution' for struggling boys of color and has led to the recruitment of more male of color teachers. While not arguing against the merits of mentorship, this article critiques what the author deems 'corrective representations. ' Corrective representations are the imagined embodiment of proper and productive masculinities that male of color educators are asked to perform. This discourse perpetuates confining representations of identity and locates the problem of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…However, considering their relationship to the political economy, nonprofit structures, and the transformation of public education under market-based reforms, youth work sites are incentivized to function more like schools (Baldridge, 2014). For instance, these organizations face pressure to align their work to neoliberal measures of academic success that require deficit framing about minoritized youth and youth workers (Kwon, 2013; Singh, 2018). This reality makes their autonomy from schools dubious in that the same macro political structures that shape schools also influence youth work spaces.…”
Section: Paradox and Complexity Within Community-based Youth Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, considering their relationship to the political economy, nonprofit structures, and the transformation of public education under market-based reforms, youth work sites are incentivized to function more like schools (Baldridge, 2014). For instance, these organizations face pressure to align their work to neoliberal measures of academic success that require deficit framing about minoritized youth and youth workers (Kwon, 2013; Singh, 2018). This reality makes their autonomy from schools dubious in that the same macro political structures that shape schools also influence youth work spaces.…”
Section: Paradox and Complexity Within Community-based Youth Workmentioning
confidence: 99%
“…Scholarship about the impact of neoliberal education restructuring holds important implications for CBES (Baldridge, 2019). Recent research about CBES has included the study of neoliberalism, governmentality, and race—pushing the field of education to consider the dangers of neoliberal control over community-based youth programming via mentoring programs, technological innovation programs, college preparation, and organizing spaces (Baldridge, 2014; Chang, 2020; Clay, 2019; Kwon, 2013; Nygreen, 2017; Singh, 2018). This work also connects to scholarship on trends in philanthropy that are often rooted in Whiteness and paternalism (Brown, 2016; Kohl-Arenas, 2015) and creates complicated relationships with organizations that can lead to mission drift or contradictions in the racial framing of youth work or difficult decisions based on the “strings” attached to philanthropic giving illustrated earlier by Gia (Gilmore, 2007; Kohl-Arenas, 2015).…”
Section: Where Do We Go From Here?mentioning
confidence: 99%
“…For students of color, having a same race and ethnicity teacher can promote this confidence building and identity development because students can relate to or identify with said teacher and see him or her as a role model and, at times, like being around an older sibling or relative (Brockenbrough, 2008). Research finds this is especially true for Black (Brockenbrough, 2008) and Latinx (Singh, 2018) male students and has been referred by research as “otherfathering” (Lynn, 2006). Therefore, as students of color develop their identities by having teachers of the same race and ethnicity, they connect better with both teachers and school, and hence this connection leads to an increased desire to be at school—hence reducing absenteeism.…”
Section: Introductionmentioning
confidence: 99%
“…Male teachers of color are underrepresented in nearly every PK-12 subject area (Singh 2018;Vilson 2015;Waite, Mentor, and Bristol 2018). While it is possible that males of color are less interested in entering the teaching profession when compared to other demographic groups, research has suggested that the underrepresentation of males of color in the teacher workforce is a reflection of ethnoracial and gendered messages about teaching and learning that male students of color encounter in schools (Fergus 2009;Howard 2008); inadequate recruitment and retention efforts in teacher education programs (Woodson and Pabon 2016); and poor professional support and limited mentoring for this population (Bristol and Goings 2019;Rezai-Rashti and Martino 2010).…”
Section: Introductionmentioning
confidence: 99%